Komunikasi Terapeutik Perawat Melalui Pendekatan Budaya - Fajar Vilbra Ayu Lestari; Rini Rachmawaty; Suni Hariati (Journal of Telenursing (JOTING), 2023)
The purpose of this review is to determine the application of nurse therapeutic communication in various cultures. This review method uses an integrative review research methodology modified by Whittemore & Knafl in 2005. This research uses an Integrative Review design, using five databases, namely PubMed, Science Direct, ProQuest, Cochrane Library and DOAJ. Publication assessment uses critical appraisal designed by Bowling (2001). The results of the review showed that 5 articles were included in the analysis. Barriers to nurse communication were found, namely language differences, inadequate language translators, lack of education and communication training for nurses, fatigue and high nurse workload. Efforts to improve nurse communication include the need to improve communication and cultural skills as well as the need for translators/mediators to help nurses communicate with patients who come from different cultures. In conclusion, there were many obstacles found in nurse-patient communication originating from various cultures throughout the world so that a further cultural approach was needed to improve the quality of nurses' therapeutic communication. Keywords: Therapeutic Communication, Cultural Approach, Nurse